The Supply Chain Management Practices of the Ship Repair Industry in Colombo Dockyard: Literature Review - Karunatilleke, Anna Weerakoon (LPPM AKMI SUAKA BAHARI CIREBON, 2025)
Abstract Purpose – This study investigates the relationships between employee involvement, partnership management, and supply chain performance in Sri Lanka’s ship repair industry, focusing on Colombo Dockyard Ltd (CDL). Methodology – Using a literature review, the research describes supply chain processes, procurement practices, and competitive dynamics within the dockyard’s operations. Data were collected through document analysis, literature review, and process mapping, supported by visual tools such as flowcharts and gap analysis frameworks. Findings – The study identifies critical challenges such as dependence on imported marine materials, price fluctuations, and inefficient procurement timelines. A key structural barrier highlighted is the lack of local manufacturing capabilities, which impacts cost and responsiveness. Despite these constraints, the study reveals opportunities for improvement through strategic partnerships, localized sourcing, and integrated supply chain models. Originality – By providing evidence-based insights, this research contributes to the development of sustainable, competitive strategies for medium-sized ship repair yards in South Asia and offers policy-level recommendations for sectoral development.